2020
DOI: 10.21203/rs.3.rs-53254/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The New Zealand Podiatry Profession – A Workforce in Crisis?

Abstract: BackgroundThis is the first study to explore workforce data from the Podiatrists Board of New Zealand. The study analysed data from an online survey, New Zealand podiatrists complete as part of their application for an Annual Practising Certificate.MethodsSurvey responses between 2015 and 2019 were analysed. Data was related to work setting, employment status, work hours, location, professional affiliations, and number of graduates entering practice. Survey data was downloaded by a second party who provide da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is currently limited research that has investigated the sustainability of the NZ podiatry workforce. Carroll et al concluded that the NZ podiatry workforce is in crisis and demonstrated there were a smaller number of podiatrists working outside of major urban cities (Auckland, Wellington, Christchurch) (18). However, this research provided no insight into the rural workforce.…”
Section: Introductionmentioning
confidence: 82%
“…There is currently limited research that has investigated the sustainability of the NZ podiatry workforce. Carroll et al concluded that the NZ podiatry workforce is in crisis and demonstrated there were a smaller number of podiatrists working outside of major urban cities (Auckland, Wellington, Christchurch) (18). However, this research provided no insight into the rural workforce.…”
Section: Introductionmentioning
confidence: 82%
“…There is currently limited research that has investigated the sustainability of the NZ podiatry workforce. Carroll et al, who analysed the NZ podiatry workforce data between 2015 and 2019 concluded that the NZ podiatry workforce is in crisis and demonstrated there were a smaller number of podiatrists working outside of major urban cities (Auckland, Wellington, Christchurch) [23]. However, this research provided no insight into the rural podiatry workforce.…”
Section: Introductionmentioning
confidence: 86%